The comprehensive pathophysiological changes in a novel rat model of postinflammatory visceral hypersensitivity. Issue 12 (28th September 2019) - Ma, Jing; Li, Jianhui; Qian, Meirui; He, Nan; Cao, Ying; Liu, Yaping; Wu, Kaichun; He, Shuixiang
Abstract : So far, a comprehensive animal model that can mimic both the central and peripheral pathophysiological changes of irritable bowel syndrome (IBS) is lacking. Here, we developed a novel IBS rat model combining trinitro‐benzene‐sulfonic acid (TNBS) and chronic unpredictable mild stress (CUMS) (designated as TC‐IBS) and compared it with the TNBS‐induced and CUMS‐induced models. TC‐IBS showed a pronounced depression phenotype with increased corticotropin‐releasing hormone receptor (CRHR)1 and CRHR2 expression at the frontal cortex and increased serum ACTH concentration. Visceral hypersensitivity (VH), as evidenced by colorectal distention (CRD) test, was highest in TC‐IBS, accompanied by increased serum 5‐hydroxytryptamine (5‐HT) level and colonic 5‐HT receptor 3A (5‐HT3A R)/5‐HT receptor 2B expression, impaired tight junction protein expression including occludin, zonula occludens‐1, and phosphorylated myosin light chain. Palonosetron, a second generation of 5‐HT3A R antagonist, alleviated VH significantly in TC‐IBS. 16S rRNA sequencing showed that TNBS plus CUMS induced a significant disturbance of the gut microbiota. Cytokine profile analysis of TC‐IBS model indicated an innate immune activation both in serum and colonic mucosa. Further, fecal microbiota transplantation improved VH and some pathophysiological changes in TC‐IBS. In summary, we established a postinflammatory IBS model covering multifactorial pathophysiological changes, which may help to develop therapies that target specific IBS subtype.—Ma, J., Li, J., Qian, M., He, N., Cao, Y., Liu, Y., Wu, K., He, S. The comprehensive pathophysiological changes in a novel rat model of postinflammatory visceral hypersensitivity. FASEB J. 33, 13560‐13571 (2019). www.fasebj.org